Assessing psychological needs in female cancer patients: a tailored model: Psychosocial assessment for female cancer - Miraglia Raineri, Alessandra; Lauro Grotto, Rosapia; Fioravanti, Giulia; Casale, Silvia; Rotella, Francesco; Fei, Leonardo; Villanucci, Alessandro; Amunni, Gianni; Faravelli, Carlo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Psychosocial needs in cancer patients seem to be underestimated and undertreated. The present research was designed to explore under-considered psychosocial needs (e.g., stressful life events, perceived social support, sense of mastery and depressive/anxious symptoms) of a female cancer group. The aim of the study was to test an assessment psycho-oncological model for female cancer patients. An assessment model of psychosocial needs and Stressful Life Events was operationalized and tests its predictive power. Methods. We used Discriminant Analysis to test predictive power of the model and of the single variables included in it. 236 oncological patients (mean age 55.50 ± 13.09) were matched with 232 healthy control groups in the study. The following instruments were chosen: the Florence Psychiatric Interview, Hospital Anxiety Depression Scale, Multidimensional Scale of Perceived Social Support, Beck Depression Inventory I, and Sense of Mastery. Results. The model satisfied the assumption criteria and was significant (Ʌ= .680, X2 = 109.73, p< .001). Conclusions. Stressful events, depression and anxiety were adequate markers of the assessment psycho-oncological model proposed for female cancer patients. The present study provides contributions in a clinical perspective: the results support the relevance of considering an assessment psychosocial model to use in female oncology for an accurate estimation of the women’s needs. Women affected by female cancer with an history of Stressful Early and Recent life events and high level of anxiety and depression could positively benefit from a psychotherapy treatment.